Intracellular uropathogenic Escherichia coli are undetectable in urinary bladders after oral mecillinam treatment: An experimental study in a pig model of cystitis. (December 2022) - Stærk, Kristian; Grønnemose, Rasmus Birkholm; Palarasah, Yaseelan; Lund, Lars; Andersen, Thomas Emil
Abstract: Objectives: Experiments in murine models of urinary tract infection (UTI) show that uropathogenic Escherichia coli (UPEC) form bacterial reservoirs in the bladder tissue that can survive beta lactam antibiotics and give rise to reinfection. The observed reinfection cascade suggests intracellular bacterial persistence as a possible explanation for recurrent UTI in humans. To test this hypothesis in an animal model closer to humans, we here investigated whether UPEC infecting the bladders of experimentally inoculated pigs are able to survive standard oral mecillinam treatment. Moreover, we analyzed the infected pig bladders by microscopy for the presence of intracellular UPEC colonies. Methods: Seven pigs were experimentally inoculated with the UPEC cystitis strain, UTI89, to induce cystitis. After 5 days of infections, a 3-day oral treatment with the extracellularly active β-lactam, mecillinam, was initiated. The infection was monitored with regular urine and blood samples. When terminated, whole bladders were removed and homogenized to quantify viable intracellular bacteria. In addition, two pigs were inoculated with UTI89pMAN01 constitutively expressing green fluorescent protein and the bladders subsequently analyzed by microscopy for bacterial location and morphology. Results: Experimental inoculation resulted in cystitis in all animals. After 3-day treatment with mecillinam, no viable UPEC were detectable in urine or bladder homogenates. Microscopy analysis of pig bladders at 12 h post infection, revealed no detectable intracellular bacterial colonies and no filamentous UPEC phenotypes were identified. Conclusions: Pigs experimentally infected with UPEC completely clear their infection upon mecillinam treatment, which contrasts earlier findings from similar experiments in mice. Moreover, the hallmarks of induced UTI in mice, i.e. intracellular bacterial communities and bacterial filamentation, could not be identically reproduced in a pig model of acute UTI. This result suggests that significant differences might exist between UTI in mice and larger mammals, and therefore perhaps also between mice and humans. Additional studies are needed to reveal details on the Escherichia coli acute UTI pathogenesis cascade in larger mammals to assess to which extent observations in mice can be transferred to humans. Graphical abstract: Image 1 Highlights: Oral mecillinam effectively clears uropathogenic E. coli from the bladder of pigs. Viable bacteria are undetectable in homogenized bladder tissues. Intracellular bacterial communities are undetectable after 12 h cystitis in pigs. Hallmarks of E. coli pathogenesis in mice could not be reproduced in pigs.